2020
DOI: 10.1016/j.msea.2019.138856
|View full text |Cite
|
Sign up to set email alerts
|

Element partitioning and electron backscatter diffraction analysis from feeding wire to as-deposited microstructure of wire and arc additive manufacturing with super duplex stainless steel

Abstract: The redistribution of alloying elements and the crystallographic characterizations in wire and arc additive manufactured (WAAM) super duplex stainless steel (SDSS) was investigated from the wire to the final as-deposited structure. The results showed that elemental partitioning between austenite and ferrite was suppressed in the last layer and the solidified droplet. The high Ni content but low Cr and N contents in the initial state of the intragranular austenite (IGA) confirmed the predominance of the chromiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The Taylor factor distribution obtained by the EBSD is also studied to evaluate the resistant ability to the plastic deformation of crystals [ 44 ]. Figure 12 shows the Taylor factor distribution maps for loading direction in the tensile tests.…”
Section: Resultsmentioning
confidence: 99%
“…The Taylor factor distribution obtained by the EBSD is also studied to evaluate the resistant ability to the plastic deformation of crystals [ 44 ]. Figure 12 shows the Taylor factor distribution maps for loading direction in the tensile tests.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated in this and other studies that additive manufacturing can be used to build DSS components, although achieving a desired microstructure and properties can be a challenge, as discussed in the introduction [ 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 ]. Figure 12 summarizes some important factors during production, the tools available to predict the resulting microstructure, and important properties that need to be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, an excessive amount of ferrite was a problem in the microstructures of the additively manufactured parts, and a post-heat treatment was necessary to balance ferrite and austenite fractions. Wire-arc additive manufacturing (WAAM) of DSS has also attracted widespread interest due to the affordable equipment and its high deposition rate [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Zhang et al [ 22 ] observed an unbalanced microstructure with a high fraction of austenite in WAAM of super DSS.…”
Section: Introductionmentioning
confidence: 99%
“…In powder bed fusion AM with selective laser melting (SLM) [9,[17][18][19], an excessive amount of ferrite formation is a problem and post-heat treatment has been necessary to balance the ferrite and austenite ratio. Wire-arc additive manufacturing of DSS has also attracted widespread interest due to the affordable equipment and its high deposition rate [20][21][22][23][24].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%